Post-Pregnancy Factors Predicting Teen Mothers' Educational Attainment by Age 30 in Two National Cohorts. Issue 8 (November 2022) - Maslowsky, Julie; Stritzel, Haley; Gershoff, Elizabeth T.
Women who begin childbearing as teenagers attain lower levels of education than women who delay childbearing until age 20 and later. Little is known about post-pregnancy factors that predict educational attainment among teen mothers. The current study examined whether teen mothers' environment and experiences 2 years after their first birth contribute to their educational outcomes by age 30, net of selection factors associated with teenage childbearing. Data were from two cohorts, the National Longitudinal Surveys of Youth 1979 ( N  = 241) and 1997 ( N  = 378). Multinomial logistic regression modeling was used to assess associations of post-pregnancy factors with teen mothers' educational attainment. Having child care was associated with increased odds of attaining a high school diploma and of attending college in both cohorts. Providing regular and subsidized child care for teen mothers is an opportunity to support teen mothers in achieving higher levels of educational attainment.